2002
DOI: 10.1002/1615-9861(200206)2:6<624::aid-prot624>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Clonal proteomics: One gene - family of proteins

Abstract: The work presented here attempts to consolidate our knowledge on cellular transcriptome and proteome. It takes into account that a typical activated cell (lymphocyte) contains 40 000 mRNA molecules at any time, and it represents about 5000 different molecular species of transcripts. Such a cell has about 1 000 000 000 protein molecules, some of them being present at 10 000 000 copies while others at a very low copy number (say 1 to 10 copies per cell). By studying cell free expression of individual cDNA clones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 31 publications
0
32
0
Order By: Relevance
“…Many proteins undergo post-translational modifications which play an important role in their activity and subcellular localization. 9,10) In this research, we demonstrate the impact of salinity on some photosynthetic parameters, AG content, and protein profiling in A. paniculata. In addition, the present article aims to get insights into the changes in osmotic composition of the plant associated with the salt acclimation.…”
Section: )mentioning
confidence: 61%
“…Many proteins undergo post-translational modifications which play an important role in their activity and subcellular localization. 9,10) In this research, we demonstrate the impact of salinity on some photosynthetic parameters, AG content, and protein profiling in A. paniculata. In addition, the present article aims to get insights into the changes in osmotic composition of the plant associated with the salt acclimation.…”
Section: )mentioning
confidence: 61%
“…Therefore, these results are necessary to examine the salt stress at the molecular level and to investigate the relationship between biomarkers (such as protein bands) and germination indices changes. Many proteins undergo post-translational modifications, which play an important role in their activity and subcellular allocation (Graves & Haystead, 2002;Kettman et al, 2002). In this research, we demonstrate the impact of salinity on some germination indices in M. officinalis.…”
Section: Introductionmentioning
confidence: 57%
“…Lefkovitz et al [15] in a similar study arrived at an estimate of 4000 proteins. A subsequent study from the same laboratory [16] identified 5000 RNA transcripts in a lymphocyte activation experiment. Hashimoto et al [17] used SAGE (serial analysis of gene expression) to look at sequences expressed by different leucocytes, and concluded that there were 27,000 tags representing unique genes expressed in leucocytes of different types.…”
Section: What Remains To Be Achievedmentioning
confidence: 99%